Endogenous Hydrogen Sulfide Persulfidates Caspase-3 at Cysteine 163 to Inhibit Doxorubicin-Induced Cardiomyocyte Apoptosis. (4th May 2022) - Ye, Xiaoyun; Li, Yingying; Lv, Boyang; Qiu, Bingquan; Zhang, Shangyue; Peng, Hanlin; Kong, Wei; Tang, Chaoshu; Huang, Yaqian; Du, Junbao; Jin, Hongfang
Abstract : Doxorubicin (DOX) is an efficient antitumor anthracycline drug, but its cardiotoxicity adversely affects the prognosis of the patients. In this study, we explored whether endogenous gasotransmitter hydrogen sulfide (H2 S) could protect against DOX-induced cardiomyocyte apoptosis and its mechanisms. The results indicated that DOX significantly downregulated endogenous H2 S production and endogenous synthetase cystathionine γ -lyase (CSE) expression and obviously stimulated the apoptosis in H9C2 cells. The supplement of H2 S donor sodium hydrosulfide (NaHS) or overexpression of CSE inhibited DOX-induced H9C2 cell apoptosis. DOX enhanced the activities of caspase family members in cardiomyocytes, while NaHS attenuated DOX-enhanced caspase-3, caspase-2, and caspase-9 activities by 223.1%, 73.94%, and 52.29%, respectively. Therefore, taking caspase-3 as a main target, we demonstrated that NaHS or CSE overexpression alleviated the cleavage of caspase-3, suppressed caspase-3 activity, and inhibited the cleavage of poly ADP-ribose polymerase (PARP). Mechanistically, we found that H2 S persulfidated caspase-3 in H9C2 cells and human recombinant caspase-3 protein, while the thiol-reducing agent dithiothreitol (DTT) abolished H2 S-induced persulfidation of caspase-3 and thereby prevented the antiapoptotic effect of H2 S on caspase-3 in H9C2 cells. The mutation of caspase-3 C148S and C170S failed to block caspase-3 persulfidation by H2 S in H9C2 cells. However, caspase-3 C163S mutation successfully abolished the effect of H2 S on caspase-3 persulfidation and the corresponding protection of H9C2 cells. Collectively, these findings indicate that endogenous H2 S persulfidates caspase-3 at cysteine 163, inhibiting its activity and cardiomyocyte apoptosis. Sufficient endogenous H2 S might be necessary for the protection against myocardial cell apoptosis induced by DOX. The results of the study might open new avenues with respect to the therapy of DOX-stimulated cardiomyopathy.